2011
DOI: 10.4314/pamj.v9i1.71216
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated infections due to Immune Reconstitution Inflammatory Syndrome after Highly Active Antiretroviral Therapy - Report of 3 cases from Nigeria

Abstract: Immune Reconstitution Inflammatory Syndromes (IRIS) are exaggerated pathological inflammatory reactions occurring after initiation of highly active antiretroviral therapy (HAART) due to exuberant immune responses to occult or apparent opportunistic infections or cancers. In view of paucity of studies from Nigeria, we report 3 cases of IRIS presenting as disseminated infections in HIV-1 infected patients initiating HAART. The first case was a previously healthy female who developed disseminated tuberculosis aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A large number of cases of HZ as a manifestation of IRIS have been reported. 4,5 GD in our case may have reflected a relatively low viral load in the affected areas.…”
Section: Multiple Dermatomal Granulomatous Dermatitis Concurring With Herpes Zostermentioning
confidence: 67%
“…A large number of cases of HZ as a manifestation of IRIS have been reported. 4,5 GD in our case may have reflected a relatively low viral load in the affected areas.…”
Section: Multiple Dermatomal Granulomatous Dermatitis Concurring With Herpes Zostermentioning
confidence: 67%
“…Immune reconstitution inflammatory syndrome is an inflammatory disease and is the consequence of an exaggerated dysregulated immune antigen interaction following highly active antiretroviral therapy (HAART) induced immune restoration. 4 The disseminated clinical presentation may probably be due to a low CD4 count as well as a high antigen burden prior to HAART initiation. 4 Nacher et al 5 reported that patients taking HAART were more likely to develop DH than untreated patients.…”
Section: Discussionmentioning
confidence: 99%
“… 4 The disseminated clinical presentation may probably be due to a low CD4 count as well as a high antigen burden prior to HAART initiation. 4 Nacher et al 5 reported that patients taking HAART were more likely to develop DH than untreated patients. The exacerbation of skin and laryngeal symptoms in our patient after starting HAART may be due to an exaggerated cell-mediated inflammatory response.…”
Section: Discussionmentioning
confidence: 99%